Excitation control: balancing PSD-95 function at the synapse - Keith, Dove J.; El-Husseini, Alaa (Frontiers in Molecular Neuroscience, 2008)
Excitability of individual neurons dictates the overall excitation in specifi c brain circuits. This process is thought to be regulated by molecules that regulate synapse number, morphology and strength. Neuronal excitation is also infl uenced by the amounts of neurotransmitter receptors and signaling molecules retained at particular synaptic sites. Recent studies revealed a key role for PSD- 95, a scaffolding molecule enriched at glutamatergic synapses, in modulation of clustering of several neurotransmitter receptors, adhesion molecules, ion channels, cytoskeletal elements and signaling molecules at postsynaptic sites. In this review we will highlight mechanisms that control targeting of PSD-95 at the synapse, and discuss how this molecule infl uences the retention and clustering of diverse synaptic proteins to regulate synaptic structure and strength. We will also discuss how PSD-95 may maintain a balance between excitation and inhibition in the brain and how alterations in this balance may contribute to neuropsychiatric disorders.